FUZZY APPROACH IN PROCESS OF MULTIPLE-ATTRIBUTE DECISION MAKING - Usenik, Janez (Journal of Energy Technology, 2024)
In the decision making problems the decision maker makes a choice based on how each possible action affected a single variable or attribute. But in many real situations the action chosen depends on how each possible action affects more than one attribute. Such problems of the decision making with multiple objectives are called multiattribute (or multipleͲattribute) decision making. In general in decision methods we assume that values are crisp numbers. However, most of the real multiattribute decisionͲmaking problems contain mixture of fuzzy and crisp data. In some cases several of the valuesthat certain alternatives take by particular criteria are not given quantitatively but represent fuzzy numbers. The method for solving fuzzy multiattribute decisionͲmaking problems consists of two steps. In the first step, the linguistic terms are transformed into crisp scores. In the second step, any of the classical multiattribute decisionͲmaking methods for obtaining the final rank of the considered alternatives can be applied. In this article is given a decisionͲmaking problem for multiple attributes; at the end we have a numerical example.